ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN MOTIVATING UNIVERSITY UNDERGRADUATE STUDENTSTOWARDS A LEARNING TASK IN PUBLIC SECTOR UNIVERSITIES OF RAWALPINDI CITY - Zarqa Farooq Hashmi; Muhammad Arshad Dahar; Ashar Sharif (Salewangang Institut Publishing, 2018)
Over the past few years, information and communication technology has become constantly used in the education especially in the schools, colleges and universities. At the age of globalization technology has its impact upon almost all aspects of life. The purpose of this paper is to explore the role of information and communication technology (ICT) in the motivating University students. The main objectives of the study were to assess motivational features of information and communication technologies as perceived by students. The independent variable of the study was ICT and dependent variable was student’s motivation. Questionnaire was used in the study to collect data. The type of research was survey descriptive research. The sample size of 340 undergraduate students was selected through simple random sampling. Descriptive statistics mean, standard deviation, frequency and percentage were used in the study.Inferential statistics i.e., chi square test was employed for statistical analysis of the data through SPSS. The findings of the study show that ICT effects students’ motivation and improves their learning; knowledge retention and understanding.ICT can solve the problems of the students and motivates students.